2019
DOI: 10.20885/jaai.vol23.iss1.art5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of accountability, transparency, affective and cognitive trust toward the interest in paying zakat

Abstract: This research aimed to expand the previous study by investigating the role of two dimensions of trust concepts, namely affective trust and cognitive trust. Particularly, this research was to analyze the influence of accountability and transparency on affective and cognitive trusts. Moreover, the purpose of this research was to test the influence of cognitive and affective trust on the interest in paying zakat through zakat institution. The subject of this research was 100 muzakkis of BAZNAS (Badan Amil Zakat N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 13 publications
3
22
1
2
Order By: Relevance
“…Transparency does not only fulfill the need for external parties, but also the internal organization environment. However, the results of this study are different from Ikhwanda and Hudayati (Ikhwandha, M & Hudayati, 2019), who found that transparency was not proven to affect muzakki beliefs because cultural norms and values in society maybe more dominant in influencing muzakki than the ZMO factors.…”
Section: Figure 3 Sem Model Of Determinants Of Muzakki Intention To Pcontrasting
confidence: 99%
See 1 more Smart Citation
“…Transparency does not only fulfill the need for external parties, but also the internal organization environment. However, the results of this study are different from Ikhwanda and Hudayati (Ikhwandha, M & Hudayati, 2019), who found that transparency was not proven to affect muzakki beliefs because cultural norms and values in society maybe more dominant in influencing muzakki than the ZMO factors.…”
Section: Figure 3 Sem Model Of Determinants Of Muzakki Intention To Pcontrasting
confidence: 99%
“…At least there are four novelties offered in this research. First, most of the previous studies analyzed the increase in zakat funds from the ZMO perspective (for examples, Coryna and Tanjung (2015); Triyawan and Aisyah (2016); Yuliafitri and Khoiriyah (2016); Yusrizal et al (2017); Yazid (2019); and Wahyudin et.al (2018), while this study directly examines from the perspective of the muzakki (Ikhwandha and Hudayati (2019). Second, this research emphasizes on profession zakat as ZMOs have not successfully managed it optimally (Astuti and Zulkifli (2018);Febriani and Siswajanty (2019).…”
Section: Introductionmentioning
confidence: 90%
“…The difference between this research and that of Ikhwanda and Hudayati (2019) is that in Ikhwanda and Hudayati (2019) both trusts were influenced by transparency and accountability, whereas this study predicted that both trust were influenced by the distributive justice of zakat. To expand Ikhwanda and Hudayati (2019) this study also examined the role of cognitive and affective trust as an intervening variable on the relationship between distributive justice and intention to pay zakat through ZIs. Ikhwanda and Hudayati (2019) only examined the indirect effect of transparency and accountability on the interest in paying zakat through zakat institutions.…”
Section: Introductionmentioning
confidence: 56%
“…Although trust has been widely studied as a factor that influences the intention to pay zakat, the concept of trust can actually be divided into cognitive trust and affective trust. Not many studies have examined the effect of cognitive and affective trust on the intention to pay zakat through ZIs except for a research conducted by Ikhwanda and Hudayati (2019). Therefore, this study also examined the effect of these two types of trust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation